Respuesta :
Answer:
y = -3x +4
Step-by-step explanation:
Using the expression for y, we can substitute that into the second equation:
... x + (1/3)(-3x +4) = 4/3
... 4/3 = 4/3 . . . . . simplify (True for any value of x.)
These equations are dependent and have an infinite number of solutions.
Answer: The system has an infinite number of solutions.
Step-by-step explanation: We are given to use the substitution method to solve the following system of linear equations :
[tex]y=-3x+4~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\\\x+\dfrac{1}{3}y=\dfrac{4}{3}~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
Substituting the value of y from equation (i) in equation (ii), we get
[tex]x+\dfrac{1}{3}(-3x+4)=\dfrac{4}{3}\\\\\\\Rightarrow x-x+\dfrac{4}{3}=\dfrac{4}{3}\\\\\\\Rightarrow \dfrac{4}{3}=\dfrac{4}{3},[/tex]
which is always true.
So, the given system of equations will have an infinite number of solutions.
Let x = k, then from equation (i), we get
[tex]y=-3k+4.[/tex]
Thus, all the solutions of the given system are
(x, y) = (k, -3k + 4), where k is any real number.